PENGARUH DUKUNGAN SOSIAL TERHADAP KESEJAHTERAAN PSIKOLOGI REMAJA DI KOTA KUPANG - Banfatin, Dewi; Lao, Hendrik (Lafadz Jaya Publisher, 2024)
Adolescence is a crucial transitional period in a person’s life, marking the shift from childhood to adulthood. During this time, social support plays a vital role in shaping an adolescent’s psychological well-being. Social support from parents, for instance, provides physical and psychological comfort, helping teenagers feel loved, cared for, and appreciated. Several studies have shown that juvenile delinquency in Indonesia has become a growing concern and a critical social issue, leading to various forms of criminal acts. Therefore, social support is seen as a significant factor that can improve the psychological well-being of adolescents. This research aims to determine whether there is a significant influence between social support and adolescents' psychological well-being. In this study, social support is the independent variable (X), and psychological well-being is the dependent variable (Y). The research subjects involved 30 teenagers from the city of Kupang. Data analysis was performed using the regression test in SPSS 21. The results show a significant influence between the two variables, with a coefficient value of 0.871 (87.1%) and a significance level of 0.000 < 0.005. This indicates that good social support can create an environment that fosters psychological well-being in adolescents.